URBAN FARMING: ALTERNATIVE SUSTAINABLE FOOD SYSTEMS AFTER THE COVID-19 PANDEMIC - Rumanintya Lisaria Putri; Joko Sutrisno; Eko Wahyono; Moh. Saeri; Rusli Burhansyah; Supriyadi Supriyadi (AGROLAND The Agricultural Sciences Journal (e-Journal), 2023)
The Covid-19 pandemic that has occurred in Indonesia has brought many significant impacts on human life in various aspects of people's lives. Policies during the pandemic such as Work from Home (WFH) and Large-Scale Social Restrictions (PSBB) have also had a socioeconomic impact on the community, including the most basic needs, namely food. On the other hand, agricultural land that continues to be eroded for the benefit of development and the age of farmers who are on average old whose ability to grow them is declining also play a role in the decline in food. The threat of a food crisis is now gradually beginning to haunt the entire society. Based on Global Hunger Indonesia (GHI) data, the hunger rate of people in Indonesia is in the serious category even though it has decreased from 24.9% (2010) to 20.1% in 2019. Indonesia must remain vigilant against the threat of famine that can trigger various kinds of major issues such as health, social and security. Urban farming is a gardening concept by utilizing the space in the house or settlement. Based on the foregoing, urban farming is very supportive and gives positive appreciation because it has proven to provide more benefits for the community in the midst of a pandemic. A number of studies also mention that urban farming can be an ideal agricultural concept in the future. In addition to the considerable benefits of urban farming, the main challenges in urban farming are determining how to monitor, regulate, and minimize risks in environmental, economic, and socio-environmental forms and understanding how urban farming can be sustainable in urban food systems globally. Urban agriculture can increase the value of food locality and reduce the energy spent in the fruit and vegetable production process. Therefore, the city government has an important role in providing specific regulations to support the implementation of sustainable urban farming.